Lived Experiences of English Literature Teachers in A Digitalized Classroom: A Phenomenological Study - Maria Jonnalyn C. Caramay; Rolando V. Maningas; Alberto D. Yazon; Karen A. Manaig; John Frederick B. Tesoro (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
Literature is required in the Philippines' general education curriculum. Studying literature through multimedia is a new technique that is more appealing than traditional texts, which rely heavily on verbal comprehension. Multimedia enables engaging activities and allows students to research literary authors and textbooks relevant to the courses using various media and information sources. It entails teamwork and has proven to promote cooperative learning effectively. Thus, this hermeneutic phenomenological study looked into the challenges and experiences of ten (10) English Literature teachers in a digitalized classroom, such as maximizing interactive platforms in teaching literature. The researcher gathered data through written interviews, in-depth one-on-one interviews, and focus group discussions; the participants were from different private schools. The participants described their experiences in the sudden paradigm shift as a challenge. Creating their own digitalized classroom was illustrated as a difficult part of adjustment and preparation, such as setting criteria for different activities aligned with one learning objective and the appropriateness of the digital platforms for the students to learn the course thoroughly. Nonetheless, participants revealed that as part of the preparation, teachers adapt to a new paradigm shift in education, creating a digitalized classroom that provides a conducive, interactive, authentic, and exciting atmosphere. It also offers a variety of learning experiences that help learners increase motivation and comprehension and develop critical thinking, creativity, and active participation. Participants have deviated from the usual